A Study of the pH Dependence of Electronically Excited Guanosine Compounds by Picosecond Time-resolved Infrared Spectroscopy - KELLY, JOHN MOFFAT; QUINN, SUSAN (My University, 2009)
The photophysical properties of 5?-guanosine monophosphate (5?-GMP) and polyguanylic acid {poly(G)} in D2O solutions of varying pH have been studied using picosecond transient infrared absorption spectroscopy. Whereas in neutral or weakly alkaline solution only the vibrationally excited electronic ground state of 5?-GMP is observed, in acidic solution the relatively long-lived (229 ? 20 ps) electronic excited state of protonated 5?-GMP, which possesses strong absorptions at 1517 and 1634 cm-1, could be detected. The picosecond transient behaviour of polyguanylic acid in acidic solution is also very different from that of the polynucleotide in neutral solution due not only to the protonation of guanine moieties yielding the protonated excited state but because of the disruption of the guanine stacks which are present in the species in neutral solution.
PUBLISHED
Keywords: photophysical properties of 5?-guanosine monophosphate (5?-GMP); photophysical properties of 5?-guanosine monophosphate (5?-GMP)